An Objective Method for Evaluating Next-Generation Sequencing Panels. (March 2019) - Angione, Kaitlin; Gibbons, Melissa; Demarest, Scott
Purpose: Next-generation sequencing panels are particularly useful in identifying genetic diagnoses in patients with nonspecific clinical findings by allowing for analysis of many genes at once. The purpose of this study was to develop a simple, objective system to evaluate the quality of available next-generation sequencing panels. Methods: A list of potentially important features of next-generation sequencing panels generated from the literature was evaluated for accessibility and objectivity and distilled to a "core" set of quality features. This was then applied to a clinical setting using the example of epilepsy panels. Panels at 8 laboratories were rated based on several objective measures to create a scoring system that differentiated between labs in a clinically meaningful way. Results: There was substantial variability in 6 "core" test criteria, allowing for creation of a scoring system that clearly distinguished labs based on identified strengths and weaknesses of each panel. Conclusion: We have demonstrated an objective method for comparing next-generation sequencing panels that can be applied or adapted to any clinical phenotype for which genetic testing is available. This method offers an unbiased approach to determining the ideal test for a given indication at a given time.